2015
DOI: 10.4103/0970-4388.148969
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of traumatic dental injuries in patients with cerebral palsy

Abstract: Dentists should be well aware of the possible dental injuries in such patients. Preventive measure measures should be taken by health care provider to reduce traumatic exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 0 publications
2
26
1
Order By: Relevance
“…37,38 Traumatic dental injuries in CP individuals can result from mental retardation, poor motor coordination, inability to control abrupt body movements, presence of involuntary physical movements, oral pathological reflexes such as the biting reflex during feeding, spasticity in masticatory muscles, or a slower response to surrounding obstacles. 39 The prevalence of dental injuries among CP in the present study was significantly higher when compared to those without CP which is in line with the previous studies. 10,37,[40][41][42] Oral ulceration and abscess were the major oral mucosal lesions present among the children with CP which might be attributed to poor muscular coordination resulting in cheek bite and also bruxism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…37,38 Traumatic dental injuries in CP individuals can result from mental retardation, poor motor coordination, inability to control abrupt body movements, presence of involuntary physical movements, oral pathological reflexes such as the biting reflex during feeding, spasticity in masticatory muscles, or a slower response to surrounding obstacles. 39 The prevalence of dental injuries among CP in the present study was significantly higher when compared to those without CP which is in line with the previous studies. 10,37,[40][41][42] Oral ulceration and abscess were the major oral mucosal lesions present among the children with CP which might be attributed to poor muscular coordination resulting in cheek bite and also bruxism.…”
Section: Discussionsupporting
confidence: 92%
“…Similar conclusions were drawn in other studies. 4,28,37,39,40,44 Mean domain scores of P-CPQ in the present study was higher among the children with CP compared to those without CP suggestive of their poorer OHRQoL. The mean score in the present study was higher than that in a study by Abanto et al (17.28).…”
Section: Discussioncontrasting
confidence: 59%
“…5 (95% CI-1.12-16.17) for those with an overjet >4 mm. 27 The majority of patients with cerebral palsy who had TDI were also reported 16,17,25,26 Similar findings were noted in children with ADHD and ASD, with a greater number of enamel fractures in individuals with multiple disorders (Table 7). Enamel and dentine fractures were reported as the most common injury in patients with visual impairments by Bhat et al 30 and Aggarwal et al 19 while enamel fracture was the most common reported injury by Munot et al 20 and Rathore et al 21 The cause of dental injuries could only be derived from a limited number of studies in each category of SHCN (Table 8).…”
Section: Re Sultssupporting
confidence: 56%
“…Though not statistically significant, poorer oral hygiene and more frequent dental erosion and dental trauma in CP children were evident, possibly making their teeth more prone to dental caries in the primary dentition stage of growth. 9,10 Poor muscular coordination accompanied with varying degrees of mental retardation is also a possible causative factor for the increased caries occurrence in CP children.…”
Section: Discussionmentioning
confidence: 99%